The boy who saved Cleveland : based on a true story - Giblin, James; Dooling, Michael (New York : Henry Holt, 2006)
During a malaria epidemic in late eighteenth-century Cleveland, Ohio, ten-year-old Seth Doan surprises his family, his neighbors, and himself by having the strength to carry and grind enough corn to feed everyone.
A Junior Library Guild selection.
1 12 17 18 23 26 29 33 34
Keywords: Ohio -- History -- 18th century -- Juvenile fiction; Frontier and pioneer life -- Ohio -- Juvenile fiction; Self-confidence -- Juvenile fiction; Epidemics -- Juvenile fiction; Sick -- Juvenile fiction; Malaria -- Juvenile fiction; Ohio -- History -- 18th century -- Fiction; Frontier and pioneer life -- Ohio -- Fiction; Self-confidence -- Fiction; Epidemics -- Fiction; Sick -- Fiction; Malaria -- Fiction